শ্রেষ্ঠ প্রবন্ধ - রফিক, আহমদ (ঢাকা : গদ্যপদ্য, 2011)
Selected essays chiefly on Bengali literature.
গ্রন্থপঞ্জিগত নির্দেশিকা অন্তর্ভুক্ত।
Donated By Akbar Ali Khan
In Bengali.
Keywords: Bengali literature -- History and criticism